Extramedullary Plasmacytoma of the Pancreas: A Rare Entity - Alexis Smith; Hassan Hal; Elizabeth Frauenhoffer (Case Reports in Radiology)
Extramedullary plasmacytomas are plasma cell neoplasms in organs other than the bone marrow. Most are found in the upper respiratory tract. Involvement of the pancreas is rare. We report a case of pancreatic plasmacytoma in association with advanced multiple myeloma.